2017
DOI: 10.4081/mi.2017.6889
|View full text |Cite
|
Sign up to set email alerts
|

Medication adherence among Nigerians with schizophrenia: correlation between clinico-demographic factors and quality of life

Abstract: Medication adherence contributes significantly to symptom remission, recovery and wellbeing in mental illnesses. We evaluated how medication adherence correlates with clinico-demographic factors and quality of life (QoL) in a sample of Nigerians with schizophrenia. This descriptive cross-sectional study involved 160 randomly selected participants with confirmed diagnosis of schizophrenia based on MINI International Neuropsychiatric Interview. Data on socio-demographic and clinical characteristics of participan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 39 publications
8
15
0
Order By: Relevance
“…The lowest score on the social relationship domain of QoL among people with schizophrenia in our study could be due to the negative symptoms, which affect the patient's ability to live independently, to perform activities of daily living, to be socially active and maintain personal relationships. Also, it could be due to the stigma towards mental illness, which excludes the mentally ill from social life (21). In the current study, medication non-adherence was significantly and negatively associated with all domains of quality of life and with the overall quality of life, and this result was in line with the previous study [20].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The lowest score on the social relationship domain of QoL among people with schizophrenia in our study could be due to the negative symptoms, which affect the patient's ability to live independently, to perform activities of daily living, to be socially active and maintain personal relationships. Also, it could be due to the stigma towards mental illness, which excludes the mentally ill from social life (21). In the current study, medication non-adherence was significantly and negatively associated with all domains of quality of life and with the overall quality of life, and this result was in line with the previous study [20].…”
Section: Discussionsupporting
confidence: 92%
“…Also, another study done in Nigeria found that there are significant negative correlations between the overall health satisfaction, physical and psychological domains of quality of life and medication adherence: i.e. participants with poorer medication adherence were more likely to have poorer mean scores on the overall QoL, health satisfaction, physical and psychological domains [21].…”
Section: Introductionmentioning
confidence: 98%
“…Studies looking at the association between clinical variables and QoL have reported a significant association between the number of daily medication, the presence of anxiety/depression symptoms, suicidality, comorbid medical problems and general psychopathology79,34,35,36 and medication adherence 9,37. According to Akinsulore et al, the presence of depressive symptoms, negative and positive symptoms of schizophrenia and frequency of relapse also predicts greater disability in patients with schizophrenia 36…”
Section: Discussionmentioning
confidence: 99%
“…Whereas some studies have attempted to measure the relationship between the life quality with medication adherence in clients with schizophrenia and even the results of such studies provide overturning results as those of a recent study conducted by Ogunnubi et al [31] who reported that participants with poorer drug adherence were more likely to have poorer mean scores on an overall the life quality, physical health, satisfaction and psychological WHO QoL scale. In this respect, Dilla, Ciudad and Álvarez [32] who explained non-adherence can aggravate patients' occupational and social functioning, resulting in decreased the quality of life and increased use of health care resources of the society.…”
Section: Studied Variablesmentioning
confidence: 99%